The Furniture Collection Stedelijk Museum Amsterdam : 1850-2000 From Michael Thonet to Marcel Wanders - Dosi Delfini, Luca; Splinter, Monique; de Roode, Ingeborg; de Weerdt, Marijke van; van Adrichem, Jan; van Beers, Hans; van Daalen, Philip; Exhibition. Kramer vs. Rietveld. Contrasten in de meubelcollectie. Stedelijk Museum Amsterdam. 2004-05-16. 2004-08-29. In de tentoonstelling Kramer vs. Rietveld. Contrasten in de meubelcollectie, staat de meubelverzameling van het museum centraal. Directe aanleiding voor deze grootse presentatie is de publicatie van de vuistdikke bestandcatalogus The Furniture Collection 1850-2000. From Michael Thonet to Marcel Wanders (Amsterdam Rotterdam : NAI Uitgevers Rotterdam Stedelijk Museum Amsterdam, 2004)
The Stedelijk Museum Amsterdam has been building a collection of applied arts and design since 1934, and furniture is one of its most significant subsections. With designs from circa 1850 to the present, this collection places the accent on the twentieth century and now includes more than 1000 objects, chairs, sofas, tables, cabinets, screens, and sets of furniture. It is one of Europe's largest and most comprehensive collections in the field of modern furniture design. This publication provides a complete catalogue of the collection assembled by the museum between 1934 and 2000. Alongside the many examples of furniture designed by Gerrit T. Rietveld, this rich collection includes furniture by other Dutch designers, such as H.P. Berlage, K.P.C. de Bazel, Piet Kramer, Martin Visser, Gijs Bakker, Piet Hein Eek, Ineke Hans and Marcel Wanders. The holdings also extend to international classics designed, for example, by Michael Thonet, Charlotte Perriand, Alvar Aalto, Marcel Breuer, Joe Colombo, Charles & Ray Eames, Arne Jacobsen, Ettore Sottsass, Philippe Starck and Ron Arad. Besides a comprehensive overview of the collection, this catalogue includes a detailed history of the furniture collection and a survey of the many exhibitions in the field of furniture design that have been organised by the Stedelijk Museum over the years. The collection's cohesion is explored in thematic interludes.
A & E Design ; Aalto, Alvar ; Aarnio, Eero ; Aartsen, Pieter ; Af Schultén, Ben ; Albinson, Don ; Alons, Cor ; Andersen, Gunnar Aagaard ; Arad, Ron ; Azumi, Shin ; Azumi, Tomoko ; Babtist, Gerrie ; Bär & Knell Design ; Bätzner, Helmut ; Bakker, Gijs ; De Bazel, Karel P.C. ; Van den Berg, Bart ; Berkovich, Elmar ; Berlage, Hendrik P. ; Bertoia, Harry ; Béwé ; Bill, Max ; Blumer, Riccardo ; Bode, Arnold ; Boesen, Viggo ; Borkenhagen, Florian ; Borsani, Osvaldo ; Van den Bosch, Jac. ; Bot, Jac. ; Bouvrie, Jan Des ; Braakman, Cees ; Breuer, Marcel ; Brinkman, Wolff ; Van den Broecke, Floris ; Bromberg, Paul ; Burkhalter, Jean ; Cibic, Aldo ; Citroën ; Citterio, Antonio ; Colombo, Joe ; Conran, Terence ; Copray & Scholten ; Coquery, R.C. ; Coray, Hans ; Dahlström, Björn ; Descalzi, Giuseppe Gaetano ; Van Dijk, Jenneke ; Dijsselhof, Gerrit Willem ; Ditzel, Nanna ; Van Dorp, Henk ; Dumoffice ; Eames, Charles & Ray ; Eckhardt, Rob ; Eek, Piet Hein ; Eiermann, Egon ; van Eijk, Niels ; Eklöf, Gunnar ; El Ultimo Grito ; Ell, Hans ; EMS (Stalen Meubelen Fabrieken) ; Eschauzier, Frits ; Ets. Erica ; Falkenberg-Liefrinck, Ida ; Formfürsorge ; Frank, Josef ; Frewing, Nicholas ; Frieling-van Osselen, Titia ; Van Gelderen, Willem ; Geytenbeek, Gerard ; Ghyczy, Peter ; Gispen, Willem H. ; De Götzen, Giuseppe ; Grupo Austral ; Guariche, Pierre ; Gugelot, Hans ; guhl, Willy ; Gurioli, Giorgio ; Gústafsson, Sigurdur ; Hans, Ineke ; Harcourt, Geoffrey ; Hardarson, Valdimar ; Haugesen, Niels Jorgen ; Havlicek, Josef ; Haye, Frans De la ; Hirche, Herbert ; Hoffmann, Josef ; Holdaway, Bernard ; van Hoytema, Theo ; Hutten, Richard ; Hvidt, Peter ; Isokon Ltd ; Jacobsen, Arne ; Järvisalo, Jouko ; Johansson, Torsten ; Judd, Donald ; Kähönen, Hannu ; Karpf, Peter ; etc.
Literature p. 444-449
biog., bibliog. p. 433-441
Engels
boek